Gene signatures and immune correlations in Parkinson’s disease Braak stages - Rui-xue Sun; Yan Guo (European Journal of Medical Research)
Abstract Background Parkinson's disease (PD), a progressive neurodegenerative disease, still lacks disease-modifying treatment strategies. The formation of Lewy body is the typical pathological feature of PD. Pathological progression can be defined by Braak stages. However, the molecular mechanism for this ascending course of α-synuclein pathology remains unclear. Methods In this study, weighted gene co-expression network analysis (WGCNA) was used to screen Braak stage-related gene signatures, followed by the functional enrichment analysis, including gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA). The hub genes were screened through CytoHubba and Least Absolute Shrinkage and Selection Operator (LASSO) analysis. The immune cell proportion was predicted by the ImmuCellAI. Furthermore, transcription factors (TFs) and miRNAs targeting the hub genes network were constructed. After verifying hub gene expression level through independent data sets. The validated hub gene was further analyzed to elucidate the potential molecular mechanism. Results Total of 388 genes associated with Braak stages were screened out through WGCNA analysis. The KEGG analysis showed that these genes were involved in endocytosis, HIF-1 signaling pathway, synaptic vesicle cycle, dopaminergic synapse, oxytocin signaling pathway, etc. Immune infiltration analysis showed that CD4 + T cells, including nTreg, Th2, and Th17, were obviously different between different Braak stages in PD. Furthermore, eights Braak stages-related hub genes were identified, including CAMK2B, CPLX2, GAPDH, GRIN1, KCNA1, MAPK3, MAPT, and STXBP1 through the cytoHubba plugin and LASSO analysis. After verifying the expression level in three independent data sets, CPLX2 was finally identified as the most reliable Braak stages-associated hub genes in PD. Conclusions This study revealed the Braak stage-related gene signatures in PD and identified CPLX2 as a novel Braak stages-related hub gene in PD, which provided a novel target for future therapeutic interventions and disease markers. The specific molecular mechanism of CPLX2 in PD remained to be further clarified.